Construction of Gender in Visual Signs in Selected Kenyan Secondary School English Textbooks - Mutune, Fellis; Maroko, Geoffrey Mokua; Kiai, Alice Wanjira (Language Circle: Journal of Language and Literature, 2022)
Textbooks are a powerful tool for the construction of social identities. Consequently, the manner in which gender is portrayed in visuals in textbooks can greatly affect the images of males and females in the society that learners develop. If gender bias in textbooks is addressed, it would be a great accomplishment towards achieving equality in education: a fundamental goal of both Education for All (EFA) and sustainable Development Goals (SDGs). In the Kenyan context, the National Policy on Gender and Development (NPGAD) was developed to address disparities in the visibility, status, and perceived potential of males and females portrayed in textbooks. However, reviews on Kenyan textbooks suggest that subtle issues around gender representation imbalance are evident. With this mismatch between policy and practice, this paper analyses gender construction in selected visuals in Kenyan secondary schools English s from a socio-semiotic perspective. The findings revealed that males’ images transcended the females’ in selected textbooks. The study also revealed that males were assigned the actor role and were more involved in both non-transactional and transactional actional processes than females. Further, males were found to make direct gazes at the reader than females. The paper concludes that disproportionate representation of gender is evident in the selected textbooks where males are implicitly or explicitly presented as superior to females. The study recommends that gender representation be considered in the design and selection of visuals to be included in English textbooks. For those textbooks which are already in use, the Kenya Institute of Curriculum Development (KICD) could initiate review activities to improve gender parity in the visuals.